Access to Mental Health Care Among Women Veterans: Is VA Meeting Women's Needs?. Issue 4 (April 2015) - Kimerling, Rachel; Pavao, Joanne; Greene, Liberty; Karpenko, Julie; Rodriguez, Allison; Saweikis, Meghan; Washington, Donna L.
Abstract : Background: Patient-centered access to mental health describes the fit between patient needs and resources of the system. To date, little data are available to guide implementation of services to women veterans, an underrepresented minority within Department of Veteran Affairs (VA) health care. The current study examines access to mental health care among women veterans, and identifies gender-related indicators of perceived access to mental health care. Methods: A population-based sample of 6287 women veterans using VA primary care services participated in a survey of past year perceived need for mental health care, mental health utilization, and gender-related mental health care experiences. Subjective rating of how well mental health care met their needs was used as an indicator of perceived access. Results: Half of all women reported perceived mental health need; 84.3% of those women received care. Nearly all mental health users (90.9%) used VA services, although only about half (48.8%) reported that their mental health care met their needs completely or very well. Gender related experiences (availability of female providers, women-only treatment settings, women-only treatment groups, and gender-related comfort) were each associated with 2-fold increased odds of perceived access, and associations remained after adjusting for ease of getting care. Conclusions: Women VA users demonstrate very good objective access to mental health services. Desire for, and access to specialized mental health services for women varies across the population and are important aspects of shared decision making in referral and treatment planning for women using VA primary care.